PENGARUH CITA RASA, SUASANA, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI MARWAH TIRTA & RESTO 3 KABUPATEN KEDIRI - Ivan Diosani; Bayu Pramutoko; Aprilia Dian Evasari (CV SWA ANUGERAH, 2021)
In today's modern era, the development of tourism has an impact on several aspects related to tourists, such as: hotels, restaurants, transportation, entertainment, etc. With the increase in tourist visits, of course, it requires a place to eat with a concept that is as attractive as possible so that it can increase the opportunity to open a culinary business with the concept of increasing the tourism sector. This study aims to determine the Taste, Atmosphere, and Service Quality on Purchasing Decisions at Marwah Tirta & Resto 3 Kediri Regency. The analysis techniques used in this study are validity test, reliability test, correlation test, t test, F test, multiple linear regression analysis, and R2 determination. The population in this study was 38,280 and the sample used was 100 visitors using accidendal sampling technique.